Odpowiedzialność wykonawcy za szkody powstałe na terenie budowy w świetle art. 652 KC - Żołtko, Marek (My University, 2019)
Art. 652 KC stanowi, iż jeżeli wykonawca przejął protokolarnie od inwestora teren budowy ponosi on aż do chwili oddania obiektu odpowiedzialność na zasadach ogólnych za szkody wynikłe na tym terenie. Problematyka odpowiedzialności wykonawcy za szkody wyrządzone na terenie budowy wydaje się doniosła nie tylko jako zagadnienie teoretyczne wymagające analizy w świetle niejednolitych poglądów prezentowanych w doktrynie i orzecznictwie na tym tle, ale również jako praktyczna kwestia istotna z punktu widzenia podmiotów działających w branży budowlanej. W art. 652 KC ustawodawca przesądził, iż wykonawca ponosi odpowiedzialność za szkody wynikłe na terenie budowy na zasadach ogólnych. Przepisy Kodeksu cywilnego ustanawiają dwa główne reżimy odpowiedzialności za szkodę: odpowiedzialność kontraktową oraz odpowiedzialność deliktową. W pracy zaprezentowany został pogląd, iż przez pojęcie „zasad ogólnych” z art. 652 KC należy rozumieć wyłącznie reguły odpowiedzialności deliktowej, a nie kontraktowej. W pracy doktorskiej rozważono również jak należy rozumieć pojęcie „terenu budowy” w świetle art. 652 KC. Nadto, przeanalizowano również zagadnienie protokolarnej formy przejęcia terenu budowy. Ustalono, iż forma protokołu została w art. 652 KC zastrzeżona dla wywołania określonych skutków prawnych. W pracy rozważono również zagadnienie w przedmiocie szkody, za jaką odpowiedzialność ponosi wykonawca w świetle art. 652 KC.

The article 652 of Civil Code states that if the contractor takes over the construction site from the investor based on the acceptance certificate produced in the form of a protocol, he is liable to general terms for damage caused on the site until the facility is handed over. The civil liability to a contractor for damages is an essential topic for the construction industry. It is also crucial as far as the civil law doctrine and jurisprudence is concerned. In the article 652 of Civil Code the legislator settled that the contractor’s liability for damages caused on building site is based on general terms. The regulations of the Polish Civil Code provide two general kind of terms of civil liability: the contractual liability and the tort liability. The essence of the article 652 of Civil Code, stating that the contractor is liable to damage caused on building site “on general terms”, is unclear. The doctoral dissertation presents the scientific view of the author that the article 652 of Civil Code, by referring to “general terms” of contractor’s liability, refers only to the terms of tortious liability but not to the rules of contractual liability. Also the aim of the dissertation was also to establish how the notion of “construction site” shall be understood in the light of the article 652 of Civil Code. What’s more, the doctoral thesis presents the issues considering the acceptance certificate produced in the form of a protocol of taking over the construction site. The doctoral thesis discusses the types of damages which can be liquidated by application of the article 652 of Civil Code.
Liability of a Contractor for Damage Caused on Building Site in the Light of Article 652 of Civil Code
Wydział Prawa i Administracji
Keywords: odpowiedzialność wykonawcy; teren budowy; odpowiedzialność deliktowa; szkoda; protokół; liability of a contractor; building site; tort liability; damage; acceptance certificate in the form of a protocol